INTEGRASI LITERASI DIGITAL DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Repa Fajriyani Sunarya; Mahpudin; Yoyo Zakaria Ansori (STKIP Subang, 2025)
This research aims to analyze the integration of digital literacy within the implementation of the Kurikulum Merdeka (Independent Curriculum) in elementary schools through a comprehensive literature review of national academic journals. The research procedure involved collecting, classifying, and synthesizing articles related to digital literacy, teacher competencies, educational technology usage, the implementation of the Pancasila Student Profile Strengthening Project (P5), and school readiness for educational digitalization. The findings indicate that digital literacy integration in elementary schools remains uneven due to differences in teacher competencies, limited digital infrastructure, and the suboptimal managerial role of school leaders. Nevertheless, there are significant opportunities to strengthen technology-based learning through teacher training, improved infrastructure, and more targeted policy support. This study provides practical recommendations for teachers, schools, school principals, and policymakers to enhance the quality and sustainability of digital literacy–based realization of the Kurikulum Merdeka.